Routledge Handbook of State Recognition - Visoka, Gëzim (Taylor & Francis, 2019)
This new handbook provides a comprehensive and multidisciplinary overview of the theoretical and empirical aspects of state recognition in international politics. Although the recognition of states plays a central role in shaping global politics, it remains an under-researched and widely dispersed subject. Coherently and innovatively structured, the handbook brings together a group of international scholars who examine the most important theoretical and comparative perspectives on state recognition, including debates about pathways to secession and self-determination, the broad range of actors and strategies that shape the recognition of states and a significant number of contemporary case studies. The handbook is organised into four key sections: Theoretical and normative perspectives Pathways to independent statehood Actors, forms and the process of state recognition Case studies of contemporary state recognition This handbook will be of great interest to students of foreign policy, international relations, international law, comparative politics and area studies. Chapter 19 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license www.routledge.com/9780815354871